PENGEMBANGAN TEKNOLOGI PENGOLAHAN YOGHURT KERANDANG (Canavalia virosa) DAN ANALISA USAHANYA - Yeyen Prestyaning Wanita; Titiek F Djaafar; Purwaningsih . (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2011)
Processing Technology Development of Kerandang (Canavalia virosa) Yoghurt and Its Effort Analysis. Kerandang (Canalia virosa) is one of the agricultural commodities grown in the land of sand beach inYogyakarta, but the utilization is not optimal because it only fed to livestock when the protein content of the seeds reached 37%. This study aims to: 1) produce a form of refined products kerandang yoghurt; 2) know thephysicochemical characteristics; and 3) acceptance of kerandang yoghurt panellists as well as economic analysis processing. The experiment was conducted in the laboratory postharvest, BPTP Yogyakarta in March-July 2009.Experimental design used was randomized complete design with two factors and four replications. The first factor is the dilution of kerandang cider (eight and ten times the kerandang weight) and the second factor is thepercentage of sugars added (5% and 10% of the volume of kerandang juice after dilution). The results showed that the kerandang yoghurt preferred was yoghurt made with dilutions of 1:10 and sugars added 10% (P2Y). Thisyoghurt had a pH of 4, the levels of lactic acid 2.16% and 34.09 ppm HCN levels that are safe for human consumption. Kerandang processing into yoghurt is quite profitable with RC ratio value of 1.59.